The Problem of Ambiguity in the Interpretation of the Criminal Offense of Insulting a State Institution in Cases of Potential Abuse of Authority - Firman Tri Wahyuono Firman Tri Wahyuono; Said Munawar Said Munawar; Roni Sulistyanto Luhukay Roni Sulistyanto Luhukay (Journal Kompilasi Hukum, 2026)
The ambiguity in the interpretation of criminal offenses involving defamation of state institutions has the potential to trigger abuse of power in a democratic state governed by the rule of law. Freedom of expression, as a constitutional right of citizens, is often pitted against criminal provisions that protect the honor of state institutions. Problems arise when the element of “insult” is formulated vaguely and is open to various interpretations, thereby granting law enforcement officials broad discretion. The method used is normative legal research employing legislative and conceptual approaches. The research findings indicate that democracy requires guarantees of freedom of expression as the foundation for public participation and mechanisms for oversight of power. In this context, the criminal offense of insulting state institutions becomes problematic when it is formulated ambiguously and fails to meet the principles of legality and lex certa. The vagueness of the element of “insult” grants broad discretion to law enforcement officials and has the potential to lead to selective law enforcement. Philosophically, state institutions, as public entities, cannot be equated with individuals in terms of the protection of moral dignity, as state institutions are established to perform public functions that must, by their very nature, be open to criticism. In the new Criminal Code, the criminal penalty for insulting state institutions straddles the line between the goal of protecting institutions and the potential for repression. The state does indeed have an interest in maintaining the authority and functions of its institutions, but disproportionate penalties risk overstepping the bounds of what constitutes an ultimum remedium. If applied broadly and flexibly, this provision could have a chilling effect, limit the space for criticism, and open the door to abuse of power.